The correct answer for this would be -10
The answer is: [B]: " x + 3y + 10 = 0 " .
______________________________________________________
Explanation:
______________________________________________________
Note the equation for a line; in 'slope-intercept form': "y = mx + b" ;
in which "y" is isolated alone, as a single variable, on the left-hand side of the equation;
"m" = the slope of the line; and is the co-efficient of "x" ;
b = the "y-intercept"; (or the "y-coordinate of the point of the "y-intercept").
______________________________________________________
So, given the information in this very question/problem:
______________________________________________________
slope = m = (-1/3) ;
b = y-intercept = (10/3) ;
______________________________________________________
And we can write the equation of the line; in "slope-intercept form"; that is:
______________________________________________________
" y = mx + b " ; as:
______________________________________________________
" y = (-1/3)x + (10/3) " ;
______________________________________________________
Now, the problem asks for the equation of this line; in "general form"; or "standard format"; which is:
________________________________________
"Ax + By + C = 0 " ;
________________________________________
So; given:
____________________________________
" y = (-1/3)x + (10/3) " ;
____________________________________
We can multiply the ENTIRE EQUATION (both sides) by "3" ; to get rid of the "fractions" ;
→ 3* { y = (-1/3)x + (10/3) } ;
→ 3y = -1x + 10 ;
↔ -1x + 10 = 3y ;
Subtract "(3y)" from each side of the equation:
____________________________________
-1x + 10 − 3y = 3y − 3y ;
to get:
-1x + 10 − 3y = 0 ;
↔ -1x − 3y − 10 = 0 ;
→ This is not one of the "3 (THREE) answer choices given" ;
→ So, multiply the ENTIRE EQUATION (both sides); by "-1" ; as follows:
-1 * {-1x − 3y − 10 = 0} ;
to get:
______________________________________________________
→ " x + 3y + 10 = 0 " ; which is: "Answer choice: [B] ."
______________________________________________________
Note that is equation is in the "standard format" ;
→ " Ax + By + C = 0 " .
______________________________________________________
Answer:
-2n²
Step-by-step explanation:
Using the image attached:
We see that the second differences (blue ones) are all equal so we conclude that this is a quadratic sequence.
The quadratic sequence has the form:
![T_{n} = an^{2} +bn +c](https://tex.z-dn.net/?f=T_%7Bn%7D%20%3D%20an%5E%7B2%7D%20%20%2Bbn%20%2Bc)
To find the value of a we just divide second difference ( -4 ) by 2:
Now we have:
Substitute
and
into the equation above:
Since
= -2 and
= -8 , after simplification we have:
The solution of this system is:
The general term is :
![T_{n} = -2n^{2}](https://tex.z-dn.net/?f=T_%7Bn%7D%20%3D%20-2n%5E%7B2%7D)
9514 1404 393
Answer:
(c) ∠ECF and ∠BCF
Step-by-step explanation:
Complementary angles total 90°. Here, 90° angle BCE is divided by ray CF into two complementary angles. They necessarily have a total of 90°.
∠ECF and ∠BCF